SPESIASI DAN BIOAVAILABILITAS LOGAM Cu DAN Zn DALAM SEDIMEN DI PELABUHAN BENOA YANG DIAYAK BASAH DAN KERING - Agustina, Arik; Sahara, Emmy; Kunti Sri Panca Dewi, I G.A. (Jurnal Kimia (Journal of Chemistry); Vol. 8, No. 1 Januari 2014DO - 10.24843/JCHEM.2014.v08.i01.p02, 2014)
This paper discusses the speciation and bioavailability of Cu and Zn in sediments of  Benoa Bay during which the sediments were sieved in wet and dry conditions. The objective of the study was to determine the concentrations of Cu and Zn in various geochemical forms, therefore the bioavalabilities of the metals could be determined. The determination of the total concentrations of Cu and Zn in the sediments were carried out by the application of extraction with the mixture of HCl and HNO 3 (3:1). The speciations of the metals were accomplished with the sequential extraction procedure. The metals concentration measurements were  performed by Atomic Absorption Spectroscopy technique with the calibration curve method. It was found that the total Cu concentrations in sediment sieved in wet and dry conditions were  178.4144 mg/kg and 179.9797 mg/kg, respectively. The speciation results for Cu in sediment sieved in wet and dry conditions were as follow: freely, leachable and exchangeable (EFLE) fraction 0.79 and 0.49%, Fe / Mn-oxide fraction 67.75% and 58.71%; organic and sulfide fractions 24.34% and 34.71%,  while resistant fraction 2.89% and 2.82%. Therefore, the bioavalable and resistant fractions of Cu in wet sieved sediment were 92,88 % and 2.89%, respectively, while those of dried sieved were 93,92 % and 2,82%, respectively. The total Zn concentrations in sediment sieved in wet and dry conditions were  195.4015  mg/kg and 196.9482 mg/kg, respectively. The speciation results for Zn in sediment sieved in wet and dry conditions were as follow: EFLE fraction 18.83% and 17.40%, Fe / Mn-oxide fraction 35.86 and 37.65%; organic and sulfide fractions 17.16% and 31.09%,  while resistant fraction 5.76% and 4.09%. Therefore, the bioavalable and resistant fractions of Cu in wet sieved sediment were 71.85% and 5.70%, respectively, while those of dried sieved were 86.14% and 4.09%, respectively.
Keywords: speciation, bioavailability, Cu dan Zn, sediment, Benoa Bay